OnTask : Scaling the Provision of Personalised Learning Support Actions to Large Student Cohorts : final report. - Pardo, Abelardo (Australia. Dept of Education, Skills and Employment, 2020)
The project had two aims. The first one was to improve the quality of the student experience for courses with large enrolments by helping instructors to deploy so-called Personalised Learning Support Actions. The second aim was to increase the maturity of learning analytics deployments in educational institutions. Institutions are not adopting learning analytics at the expected rate mainly due to the difficulty on identifying a clear connection between the use of data and contributions to the overall institutional mission. The project articulates this connection arguing that the comprehensive data sets already existing in some institutions can Scaling the Provision of Personalized Learning Support Actions to Large Student Cohorts 6 be used to empower instructors to deploy effective feedback processes in large enrolment courses. [Publisher summary, ed]